Degradation of Stearoyl-Coenzyme A Desaturase: Endoproteolytic Cleavage by an Integral Membrane Protease - Heinemann, F. Scott (The American Society for Cell Biology, 1998)
Stearoyl-coenzyme A desaturase (SCD) is a key regulator of membrane fluidity, turns over rapidly, and represents a prototype for selective degradation of resident proteins of the endoplasmic reticulum. Using detergent-solubilized, desaturase-induced rat liver microsomes we have characterized a protease that degrades SCD. Degradation of SCD in vitro is highly selective, has a half-life of 3–4 h, and generates a 20-kDa C-terminal fragment of SCD. The N terminus of the 20-kDa fragment was identified as Phe(177). The cleavage site occurs in a conserved 12-residue hydrophobic segment of SCD flanked by clusters of basic residues. The SCD protease remains associated with microsomal membranes after peripheral and lumenal proteins have been selectively removed. SCD protease is present in normal rat liver microsomes and cleaves purified SCD. We conclude that rapid turnover of SCD involves a constitutive microsomal protease with properties of an integral membrane protein.